Long term methylphenidate exposure and growth in children and adolescents with ADHD. A systematic review and meta-analysis. (January 2021) - Carucci, Sara; Balia, Carla; Gagliano, Antonella; Lampis, Angelico; Buitelaar, Jan K.; Danckaerts, Marina; Dittmann, Ralf W.; Garas, Peter; Hollis, Chris; Inglis, Sarah; Konrad, Kerstin; Kovshoff, Hanna; et al.
Highlights: MPH is a very effective treatment for ADHD but there are concerns about potential adverse effects of extended treatment on several systems, including growth. Long term MPH appears to be associated with a statistically significant impact on height and weight in ADHD children and adolescents, but effect sizes are small, with possible minimal clinical effect. Sensitivity analysis did not reveal a significant effect of dose, age and drug naïvity condition as possible clinical moderators. Data on effect on pubertal maturation, although limited, seem to favour the exclusion of a possible drug effect on sexual maturation in ADHD subjects. Current clinical practice guidelines indicate the need of a careful assessment of growth parameters before starting stimulant treatment and the periodic monitoring using standardised growth charts. Particular caution should be taken in pre-school children. Abstract: Background: Methylphenidate (MPH) is an efficacious treatment for ADHD but concerns have been raised about potential adverse effects of extended treatment on growth. Objectives: To systematically review the literature, up to December 2018, conducting a meta-analysis of association of long-term (> six months) MPH exposure with height, weight and timing of puberty. Results: Eighteen studies (ADHD n = 4868) were included in the meta-analysis. MPH was associated with consistent statistically significant pre-post difference for both height (SMD = 0.27, 95% CI 0.16-0.38, p < 0.0001) and weight (SMD = 0.33, 95% CI 0.22-0.44, p < 0.0001) Z scores, with prominent impact on weight during the first 12 months and on height within the first 24-30 months. No significant effects of dose, formulation, age and drug-naïve condition as clinical moderators were found. Data on timing of puberty are currently limited. Conclusions: Long-term treatment with MPH can result in reduction in height and weight. However, effect sizes are small with possible minimal clinical impact. Long-term prospective studies may help to clarify the underlying biological drivers and specific mediators and moderators.